Response of irrigated corn hybrids to plant density in three sowing dates - da Silva, Paulo Regis Ferreira; Argenta, Gilbar; Rezera, Fabiana (Pesquisa Agropecuaria Brasileira, 1999)
Plant density response of corn besides influenced by hybrids traits, soil fertility level and water availability, could also vary with sowing date, since it affects plant growth and development. With the objective of determining the most adequate plant density of corn hybrids with high potential grain yields, in three sowing dates, in relation to grain yields, yield components and other agronomic traits, four experiments were conducted in the state of Rio Grande do Sul, Brazil, with complementary irrigation. The treatments were composed by four hybrids (Pioneer 3063, Pioneer 3207, XL 212 and Cargill 901), four plant densities (50, 70, 90 and 110,000 pl/ha) and three sowing dates (August, October and December). There was no response to plant density of corn hybrids tested at sowing dates of August and December. The increase in plant density was beneficial only in the sowing date of October, when the highest grain yield with 70,000 pl/ha was obtained in two growing seasons, out of regard to the hybrids tested.